2009
DOI: 10.1111/j.1529-8817.2009.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSITY AND MORPHOLOGY OF SKELETONEMA SPECIES IN SOUTHERN BRAZIL, SOUTHWESTERN ATLANTIC OCEAN1

Abstract: We examined the morphology of Skeletonema species occurring in coastal waters of southern Brazil, on the basis of LM, SEM, and TEM analyses of six isolated strains and of 13 field samples from the Patos Lagoon estuary and the adjacent Cassino Beach. We concluded that the genus Skeletonema is highly diverse in coastal waters of southern Brazil, with the occurrence of four confirmed species: S. costatum, S. pseudocostatum, S. potamos, and S. tropicum. In addition, EM details must still be provided for S. menzeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 13 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Various species have been reported to occur in coastal waters, for example, in China, Korea, Russia, Brazil, and Uruguay (Bergesch et al . ; Gonzalez–Piana & Ferrari ; Jung et al . ; Torgan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Various species have been reported to occur in coastal waters, for example, in China, Korea, Russia, Brazil, and Uruguay (Bergesch et al . ; Gonzalez–Piana & Ferrari ; Jung et al . ; Torgan et al .…”
Section: Introductionmentioning
confidence: 99%
“…S. tropicum showed the highest cell number and growth rate in the summer experiment (SiNP μ =0.74; NP μ =0.56). S. tropicum is a warm-water species (Hasle and Syvertsen, 1996) that can be found during the summer at Cassino Beach and the adjacent Patos Lagoon in southern Brazil (Bergesch et al, 2009) and in other locations (e.g., Dokai Bay, Japan) (Kaeriyama et al, 2011). Hulburt and Guillard (1968) concluded that S. tropicum would not be found in areas where the winter seawater temperature decreases to less than 15°C.…”
Section: Discussionmentioning
confidence: 98%
“…This is an agreement a previous study indicating that Skeletonema sp. grow well under wide salinity conditions in the natural environment 34,56,57 . However, C. didymus showed As biotransformation under salinities between 10–30‰, whereas below 5‰ and above 35‰, the redox reaction, as well as methylation, was absent.…”
Section: Resultsmentioning
confidence: 99%